Juhūd al-Fuqahāʾ fī Taʾṣīl al-Manhaj al-Naqlī wa Ibtikār al-Manhaj al-ʿAqlī: Ibn Rushd al-Ḥafīd min Khilāl Kitābih "Bidāyat al-Mujtahid" Namūdhaj - Jabbie, Alhassan; Sonko, Kebba Lang; Zabraman, Faisal Abdulrahman; Ceesay, Omar (Al-Zahra: Journal for Islamic and Arabic Studies, 2024)
This research aims to clarify Ibn Rushd's approach to establishing the transmitted approach and innovating the rational approach through his book Bidayat al-Mujtahid wa Nihayat al-Muqtasid. The study employs an inductive and analytical descriptive approach, utilizing library research to analyze relevant books and articles concerning the transmitted and rational methods. The findings reveal that Ibn Rushd integrated textual reasoning and rationality in his legal methodology. He recognized that reason is the foundation of obligation and a key tool for understanding. He understood that reason enables the comprehension of texts and transmitted knowledge and facilitates understanding of the Sharia. Consequently, Ibn Rushd employed reason as a tool in conducting ijtihad on controversial issues, utilizing it to achieve goodness and happiness. This paper concludes that Ibn Rushd's approach involved collecting transmitted knowledge and applying rational reasoning in matters of ijtihad. He utilized reason as a critical tool in addressing controversial issues, aiming to achieve goodness and happiness.